Tracking ancestral lineages and recent expansions of NBS-LRR genes in angiosperms. (2nd July 2016) - Shao, Zhu-Qing; Wang, Bin; Chen, Jian-Qun
ABSTRACT: Nucleotide-Binding Site-Leucine-Rich Repeat (NBS-LRR) genes are the largest plant disease resistance ( R ) gene family, accounting for ∼80% of more than 140 cloned R genes. Recently, we systematically investigated NBS-LRR genes in 22 angiosperm genomes. By performing phylogenetic analysis of these genes in major angiosperm clades separately and as a whole, we gained strong evidence supporting that angiosperm NBS-LRR genes are derived from 3 anciently separated NBS-LRR classes: RPW8-NBS-LRR (RNL), TIR-NBS-LRR (TNL) and CC-NBS-LRR (CNL). A total of 23 ancestral NBS-LRR lineages gave rise to the current NBS-LRR diversity of angiosperm through dynamic expansions. Comparative analysis of RNL, TNL, and CNL classes revealed that while RNL genes evolved conservatively to maintain its role in defense signal transduction, the latter 2 classes underwent convergent recent expansions in various plant genomes. The revealed evolutionary pattern of angiosperm NBS-LRR genes reflects a long history of competition between plant and pathogen.